Probing the structure of local magnetic field of solar features with helioseismology. Issue Volume 9:Issue S302(2013) (7th August 2014) - Daiffallah, Khalil
Abstract: Motivated by the problem of local solar subsurface magnetic structure, we have used numerical simulations to investigate the propagation of waves through monolithic magnetic flux tubes of different sizes. A cluster model can be a good approximation to simulate sunspots as well as solar plage regions which are composed of an ensemble of compactly packed thin flux tubes. Simulations of this type are powerful tools to probe the structure and the dynamics of various solar features which are directly related to solar magnetic field activity.